Control strategies for grapevine phytoplasma diseases: factors influencing the profitability of replacing symptomatic plants - PAVAN, Francesco; MORI, Nicola; BRESSAN, Sandro; MUTTON, Pierbruno (Phytopathologia Mediterranea, 2012)
The course of ‘flavescence dorée’ (FD) and ‘bois noir’ (BN) diseases can result in either recovery or death of affected grapevines. When farmers observe symptomatic grapevines, they must choose whether to replace or maintain the plants. To establish whether there is an advantage in replacing symptomatic grapevines, data were collected on the costs of replacing them (removing the diseased plants and planting new grapevines, with resultant yield loss during the rearing period) and growing them on (yield losses in symptomatic grapevines over the following years). To calculate the cost of maintaining FD-infected plants, the possibility was also considered that symptomatic grapevines may be sources of phytoplasmas for the vector Scaphoideus titanus Ball. The symptomatic course of BN was observed in ‘Chardonnay’, and of FD in ‘Chardonnay’, ‘Merlot’ and ‘Perera’ grape cultivars. The costs of replacement decreased with the increase in the productive lifetime of the vineyards. The cost of maintenance was greatly influenced by the course of the diseases, and in the case of FD, also by the risk of new infections due to the fact that S. titanus acquires phytoplasmas from infected grapevines. The replacement of plants affected by BN is not profitable when recovery is the most frequent course of the disease, particularly when it is considered that replantings can, in turn, become infected. The replacement of plants affected by FD is not profitable for cultivars with a recovery near to 100% (‘Merlot’), whereas it is necessary for cultivars where the course of the disease is frequently lethal (‘Perera’). For cultivars with intermediate sensitivity, the decision varies in relation to agronomic/economic factors and to the risk of new infections (‘Chardonnay’). For FD, both replacement and maintenance strategies need to be associated with S. titanus control inside and outside the vineyards. In the case of maintenance the infected plants can be sources of phytoplasmas, and in the case of replacement, the vector can also inoculate the new grapevines.